Three-dimensional simulation of viscous-flow agglomerate sintering - Peukert, Wolfgang; Kirchhof, Martin; Schmid, Hans-Joachim (Physical Review E, 2009)
The viscous-flow sintering of different agglomerate particle morphologies is studied by three-dimensional computer simulations based on the concept of fractional volume of fluid. For a fundamental understanding of particle sintering characteristics, the neck growth kinetics in agglomerate chains and in doublets consisting of differently sized primary particles is investigated. Results show that different sintering contacts in agglomerates even during the first stages are not completely independent from each other, even though differences are small. The neck growth kinetics of differently sized primary particles is determined by the smaller one up to a size difference by a factor of approximately 2, whereas for larger size differences, the kinetics becomes faster. In particular, the agglomerate sintering kinetics is investigated for particle chains of different lengths and for different particle morphologies each having ten primary particles and nine initial sintering contacts. For agglomerate chains, the kinetics approximately can be normalized by using the radius of the fully coalesced sphere. In general, different agglomerate morphologies show equal kinetics during the first sintering stages, whereas during advanced stages, compact morphologies show significantly faster sintering progress than more open morphologies. Hence, the overall kinetics cannot be described by simply using constant morphology correction factors such as fractal dimension or mean coordination number which are used in common sintering models. However, for the first stages of viscous-flow agglomerate sintering, which are the most important for many particle processes, a sintering equation is presented. Although we use agglomerates consisting of spherical primary particles, our methodology can be applied to other aggregate geometries as well. © 2009 The American Physical Society.
Keywords: sintering; agglomerate; simulation; kinetic; model